PENGARUH QUALITY OF WORK LIFE DAN WORK MOTIVATION DIMODERASI OLEH CHANGE MANAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada AOCC PT Angkasa Pura I (Persero)) - Marina, Rosa; Yusuf, Tabroni; Z, Zulkifli (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
This study aims to analyze the effect of Quality of Work Life and work motivation moderated by change management on organizational citizenship behavior through work engagement as an intervening variable. This type of research in this research is causality research with a quantitative method approach. The population in this study is the number of operational employees working at AOCC Branch Office of PT Angkasa Pura I (Persero) who have had a minimum working period of 2 (two) years while the sample taken was 101 people. Data collection is done by distributing questionnaires. The data analysis technique used is SEM analysis with PLS. The results in this study indicate that: (1) Quality of Work Life influences Work Engagement; (2) Quality of Work Life has no significant effect on Organizational Citizenship Behavior; (3) Work Motivation influences Work Engagement; (4) Work Motivation has no effect on Organizational Citizenship Behavior; (5) Work Engagement has no effect on Organizational Citizenship Behavior; (6) Quality of Work Life does not have a significant influence on Organizational Citizenship Behavior through Work Engagement; (7) Work Motivation does not have a significant influence on Organizational Citizenship Behavior through Work Engagement; (8) Change Management to influence the effect of Work Motivation on Organizational Citizenship Behavior.